COMPARATIVE ANALYSIS OF GRAMMATICAL CATEGORIES OF VERBS IN METAPHORS - Avezova Nigora Safarovna (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2026)
Annotation. This article presents a comparative analysis of the grammatical categories of verbs as they function in metaphorical expression. The study examines how verbal categories such as tense, aspect, mood, voice, person, and number participate in the creation of metaphorical meaning and how grammatical metaphor restructures the relationship between semantic content and grammatical form. It argues that metaphor is not only lexical but also grammatical, and that the comparison of verbal categories across metaphorical uses reveals important interactions among cognition, discourse, and linguistic structure [1][2][3].